Idea of monitoring internal processes of distributed solar inverters = Idea monitorowania wewnętrznych procesów rozproszonych inwerterów solarnych - Krysik, Miłosz; Piotrowski, Krzysztof; Rybski, Ryszard (Zielona Góra: Uniwersytet Zielonogórski, Instytut Metrologii, Elektroniki i Informatyki)
The paper presents a study aiming at analyzing the means to monitor the internal state of the parallel connected inverters and to investigate the indirect interactions between these inverters.
Keywords: komputeryzacja; przyrządy pomiarowe; informatyka; technologie informacyjne